IDENTIFICATION OF MERCURY AND HYDROQUINONE CONTENT IN HANDBODY PRODUCTS CIRCULATING IN GORONTALO CITY - Adnan Malaha; alfian S. Abas; Efendy, Aprilia Putri (LPPM Universitas Bina Mandiri Gorontalo, 2023)
This study aims to determine the presence of dangerous chemical compounds, namely mercury and hydroquinone in hand body preparations circulating in Gorontalo City. The method used in this study uses descriptive research with an observational approach and qualitative laboratory tests. From the research results, 12 samples were tested for mercury (using NaOH and KI), 4 positive samples contained mercury and 8 negative samples contained mercury. 4 samples were marked by a yellow color change in the NaOH solution and a red color in KI solution and the 8 negative samples did not change color so that these samples did not contain harmful chemicals in the handbody. From the results of the 12 samples that were subjected to the hydroquinone test (using FeCl3) the results obtained were 2 positive samples containing hydroquinone and 10 samples not containing hydroquinone. The 2 positive samples were marked by a change in green color and had precipitate in the sample, whereas in the 10 samples the results obtained had no color change and had no precipitate in the sample tested.